Screening of linear B-cell epitopes and its proinflammatory activities of Haemophilus parasuis outer membrane protein P2 - Wu, Jingbo; Nan, Wenjin; Peng, Guoliang; Hu, Honghui; Xu, Chongbo; Huang, Jianqiang; Xiao, Zhengzhong (Frontiers in Cellular and Infection Microbiology, 2023)
Haemophilus parasuis is a commensal organism of the upper respiratory tract of pigs, but virulent strains can cause Glӓsser’s disease, resulting in significant economic losses to the swine industry. OmpP2 is an outer membrane protein of this organism that shows considerable heterogeneity between virulent and non-virulent strains, with classification into genotypes I and II. It also acts as a dominant antigen and is involved in the inflammatory response. In this study, 32 monoclonal antibodies (mAbs) against recombinant OmpP2 (rOmpP2) of different genotypes were tested for reactivity to a panel of OmpP2 peptides. Nine linear B cell epitopes were screened, including five common genotype epitopes (Pt1a, Pt7/Pt7a, Pt9a, Pt17, and Pt19/Pt19a) and two groups of genotype-specific epitopes (Pt5 and Pt5-II, Pt11/Pt11a, and Pt11a-II). In addition, we used positive sera from mice and pigs to screen for five linear B-cell epitopes (Pt4, Pt14, Pt15, Pt21, and Pt22). After porcine alveolar macrophages (PAMs) were stimulated with overlapping OmpP2 peptides, we found that the epitope peptides Pt1 and Pt9, and the loop peptide Pt20 which was adjacent epitopes could all significantly upregulated the mRNA expression levels of IL-1α, IL-1β, IL-6, IL-8, and TNF-α. Additionally, we identified epitope peptides Pt7, Pt11/Pt11a, Pt17, Pt19, and Pt21 and loop peptides Pt13 and Pt18 which adjacent epitopes could also upregulate the mRNA expression levels of most proinflammatory cytokines. This suggested that these peptides may be the virulence-related sites of the OmpP2 protein, with proinflammatory activity. Further study revealed differences in the mRNA expression levels of proinflammatory cytokines, including IL-1β and IL-6, between genotype-specific epitopes, which may be responsible for pathogenic differences between different genotype strains. Here, we profiled a linear B-cell epitope map of the OmpP2 protein and preliminarily analyzed the proinflammatory activities and effects of these epitopes on bacterial virulence, providing a reliable theoretical basis for establishing a method to distinguish strain pathogenicity and to screen candidate peptides for subunit vaccines.